A FREQUÊNCIA TEMÁTICA DOS REFUGIADOS NA COMUNICAÇÃO VIRTUAL DE ORGANIZAÇÕES DESPORTIVAS (Fiep Bulletin - online, 2020)
Faced with the challenges of the 21st century regarding the means of experiencing and communicating on a global scale, technology has been used to understand the development of the 'sport and refugees' to reflect the contributions of sport to refugee issues. In order to identify the presence of the keyword "refugee" in the official electronic portals of ten International Olympic Sports Federations, belonging to Association of International Summer Olympic Federations, it was decided to choose the ten federations with greater representation on a global scale, considering the number of affiliated national federations. For the information gathering process, the word 'refugee' was initially entered in the search tool of the official website of each federation, taking into consideration that all the searched sites have the English language. Subsequently, the information was grouped into a table for a visual analytical approach and basic statistics and descriptive task. The results from the insertion of the keyword "refugee" in the different official organization's websites presented positive answers to what the research questioned - frequency of the word "refugees" as a way to understand if these organizations do not give any relevance to the theme. Of the 10 (ten) platforms investigated, 08 (eight) had positive results, 02 (two) did not provide the opportunity to search and none showed negative result that would be the absence of the word representing in this case, the refugee theme. From the analysis of the results achieved in the search engines of the websites of the most relevant sports administration entities around the world, using a statistical syllogism, since all sports administration entities that had a search engine for words, on their websites they pointed to the presence of the word 'refugee', it is possible to state that they pay any attention to the theme.
Keywords: sports; refugees; web sites